Best Practices and Lessons Learned in ICT Sector Innovation : A Case Study of Israel - Getz, Daphne (World Bank, Washington, DC, 2016)
This case study of Israel's ICT sector highlights the important role of the government in the emergence of Israel as a power house of high-tech in information and communications technology, by laying the foundations for private industry to support innovation, and through heavy investment in building the much-needed human capital resource. The main strategic asset is human resources. The quality of human capital is essential to innovation and economic growth. Skilled human resources are the most strategic assets in the knowledge society. The Israeli higher education system, mostly supported by the government, contributed a great deal to the success of Israel in the high-tech arena.